2021
DOI: 10.7759/cureus.18858
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Hospitalization for Systemic Lupus Erythematosus in Saudi Arabia Compared With the Global Setting: A Retrospective Single-center Observational Study

Abstract: Background: This study sought to evaluate the main causes of hospitalization of patients with systemic lupus erythematosus (SLE) in a tertiary health center in Saudi Arabia.Methods: A retrospective observational study was performed for all the SLE patients admitted to King Saud Medical City between 2016 and 2019. The primary reason for hospitalization was determined by the primary physician caring for the patient at the time of admission.Results: Of the 98 hospitalizations for SLE, 49% of patients were admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
1
2
Order By: Relevance
“…7 For patients requiring admission, the degree and pattern of average disease activity is comparable to other published literature. 20,21 The prevalence of NPSLE in the present study is lower than that reported in some of the previous studies from India. 10 Of the 79 patients included in the study, as per ICD-10 criteria, 50.6% of the patients were found to be suffering from at least one psychiatric comorbidity.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…7 For patients requiring admission, the degree and pattern of average disease activity is comparable to other published literature. 20,21 The prevalence of NPSLE in the present study is lower than that reported in some of the previous studies from India. 10 Of the 79 patients included in the study, as per ICD-10 criteria, 50.6% of the patients were found to be suffering from at least one psychiatric comorbidity.…”
Section: Discussioncontrasting
confidence: 73%
“…7 For patients requiring admission, the degree and pattern of average disease activity is comparable to other published literature. 20,21 The prevalence of NPSLE in the present study is lower than that reported in some of the previous studies from India. 10…”
Section: Discussioncontrasting
confidence: 64%
“…In contrast, in studies involving China, especially Shanghai, the infection rates were shown to increase at a rate of 30-50 per 100,000 people (Leong et al, 2021). At the regional level, the study of Alhassan et al (2021) revealed that the infection rate in the Kingdom of Saudi Arabia was 3.2-19.3 per 100,000. In Oman, the infection rate was range 5-63 per 100 000 inhabitants (Aladhoubi et al, 2021) .On the Turkish side, in a study of Uzuner et al (2021), the incidence was 9.73 per 100,000 people.…”
Section: Introductionmentioning
confidence: 91%